2004
DOI: 10.2337/diabetes.53.12.3217
|View full text |Cite
|
Sign up to set email alerts
|

Hyperlipidemia in Concert With Hyperglycemia Stimulates the Proliferation of Macrophages in Atherosclerotic Lesions

Abstract: Hyperglycemia and hyperlipidemia are important risk factors for diabetes-accelerated atherosclerosis. Macrophage proliferation has been implicated in the progression of atherosclerosis. We therefore investigated the effects of hyperglycemia and hyperlipidemia on macrophage proliferation in murine atherosclerotic lesions and isolated primary macrophages. Hyperglycemic LDL receptor-deficient mice that were fed a cholesterol-free diet for 12 weeks did not have elevated cholesterol levels compared with nondiabetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
84
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(91 citation statements)
references
References 48 publications
6
84
0
1
Order By: Relevance
“…A subset of LDLR Ϫ/Ϫ ;GP mice fed the low-fat diet (seven mice per group) was injected peritoneally with thioglycollate after 4 weeks of diabetes, as described in ref. 30. The monocytes/macrophages were adhesion-purified for 1 h in the presence of serum-free RPMI and harvested for Western blot analysis.…”
Section: Methodsmentioning
confidence: 99%
“…A subset of LDLR Ϫ/Ϫ ;GP mice fed the low-fat diet (seven mice per group) was injected peritoneally with thioglycollate after 4 weeks of diabetes, as described in ref. 30. The monocytes/macrophages were adhesion-purified for 1 h in the presence of serum-free RPMI and harvested for Western blot analysis.…”
Section: Methodsmentioning
confidence: 99%
“…et al [27] who found that a decrease in hyperglycemia lead to decrease in macrophage proliferation and accumulation in psoriatic lesions which could be attributed to a reduction in oxidation of LDL which might play a role in induction of macrophage recruitment to psoriatic plaques. Gyldenløve M1.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidized LDL upregulates the expression of adhesion molecules and secretion of chemokines, which contributes to the recruitment of circulating monocytes and leukocytes (Cersosimo & DeFronzo, 2006;Steinberg, 2002). One of the initial steps in the formation of atherosclerosis is the adhesion of monocytes to the endothelium, their entry into sub-endothelial space, followed by their differentiation into macrophages (Lamharzi et al, 2004). These cells are then responsible for taking up LDL and other particles, thereby starting the atherogenesis process (Lamharzi et al, 2004).…”
Section: Stress Dyslipidemia and Atherosclerosis: Putative Mechanismsmentioning
confidence: 99%